Image Registration Methode in Radar Interferometry - S. Chelbi; A. Khireddine (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
This article presents a methodology for the determination of the registration of an Interferometric Synthetic radar (InSAR) pair images with half pixel precision. Using the two superposed radar images Single Look complexes (SLC) [1-4], we developed an iterative process to superpose these two images according to their correlation coefficient with a high coherence area. This work concerns the exploitation of ERS Tandem pair of radar images SLC of the Algiers area acquired on 03 January and 04 January 1994. The former is taken as a master image and the latter as a slave image.